PROBLEMATIKA IMPLEMENTASI EKSEKUSI PADA PERKARA HAK ASUH ANAK - Harly, Agustian; Darmawan Saputra, Kurniadi; Maryani, Maryani (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2024)
This study examines the implementation of the execution of Religious Court decisions regarding child custody (hadhanah) after divorce. The main focus is on the procedures, challenges, and efforts of the court in ensuring the best interests of the child during the execution process. The methods used are literature review and normative legal analysis of related court regulations and decisions. The results of the study indicate that the execution of hadhanah decisions has a special complexity because it involves the psychological aspects of the child. The main challenges include the child's refusal, the uncooperativeness of the losing party, and the risk of hiding the child. Religious Courts must apply a wise approach, including persuasive efforts, before coercive action. Coordination between the court, law enforcement officers, and related parties is essential for effective execution. In conclusion, the execution of hadhanah decisions must always prioritize the best interests of the child, considering the involvement of child psychologists if necessary. This study recommends the development of specific guidelines for the execution of hadhanah decisions that focus on the protection and welfare of children.